Platelet-to-Portal Vein Width Ratio and Platelet-to-Spleen Thickness Ratio Can Be Used to Predict Progressive Liver Fibrosis Among Patients With HBV Infection With HBeAg-Negativity and a Normal ALT Level - Feng, Mudan; Lei, Lan; Xu, Jian; Shi, Yuzhi; Yang, Wenfeng (Frontiers in Medicine, 2022)
Background Some people infected with the hepatitis B virus (HBV) with a normal level of alanine aminotransferase (ALT) are at risk of disease progression. We evaluated the value of platelet-to-portal vein width ratio (PPR) and platelet-to-spleen thickness ratio (PSR) to predict progressive liver fibrosis among patients with HBV infection with HBV e antigen (HBeAg)-negativity and a normal ALT level. Methods HBV surface antigen (HBsAg)-positive and HBeAg-negative individuals with a normal ALT level were enrolled. The inflammation grade (G) and fibrosis stage(S) were analyzed according to pathological features. Then, two groups (<S2 vs. ≥S2) among people with a normal ALT level were divided based on the pathological diagnosis, and the clinical characteristics were summarized. Results Seventy-three individuals among 142 patients with HBsAg-positivity and HBeAg-negativity had a normal ALT level. Also, 83.56% (61/73) individuals showed progressive liver fibrosis (≥S2). The ALT level and aspartate aminotransferase (AST) between the two groups differed (21.01 ± 7.40 vs. 25.37 ± 7.90 U/L, p = 0.08; 29.49 ± 13.56 vs. 30.16 ± 21.88 U/L, p = 0.92, respectively). Portal-vein width, serum levels of albumin and globulin, AST-to-Platelet Ratio Index (APRI), and Fibrosis 4 (FIB-4) score were not significantly different between the two groups (p > 0.05). The platelet count, PPR, and PSR were significantly different between the two groups [(145.92 ± 14.55) ×109/L vs. (126.38 ± 23.85) ×109/L, p = 0.008; 10.80 ± 1.30 vs. 9.01 ± 1.97, p = 0.004; 4.21 ± 0.65 vs. 3.33 ± 0.89, p = 0.02, respectively]. The PPR and PSR decreased gradually upon fibrosis aggravation (p < 0.05). Based on the cut off value of the PPR (9.07) and PSR (3.54), their sensitivity and specificity was 0.917 and 0.525, and 0.833 and 0.541, respectively. Conclusion The PPR and PSR can be employed to assess earlier fibrosis progression among patients with HBV infection with HBeAg-negativity and a normal ALT level.